If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -10) + 6(x + -2) = 48 Reorder the terms: 2(-10 + x) + 6(x + -2) = 48 (-10 * 2 + x * 2) + 6(x + -2) = 48 (-20 + 2x) + 6(x + -2) = 48 Reorder the terms: -20 + 2x + 6(-2 + x) = 48 -20 + 2x + (-2 * 6 + x * 6) = 48 -20 + 2x + (-12 + 6x) = 48 Reorder the terms: -20 + -12 + 2x + 6x = 48 Combine like terms: -20 + -12 = -32 -32 + 2x + 6x = 48 Combine like terms: 2x + 6x = 8x -32 + 8x = 48 Solving -32 + 8x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 8x = 48 + 32 Combine like terms: -32 + 32 = 0 0 + 8x = 48 + 32 8x = 48 + 32 Combine like terms: 48 + 32 = 80 8x = 80 Divide each side by '8'. x = 10 Simplifying x = 10
| 3ct^4-3cj^2=0 | | 4x(5+2)=22 | | -9=15+b-3 | | 1/200/30 | | 100=800b+5 | | 3-(-6)+(-7)+(-4)= | | 6(m+8)+2m=35-5m | | 20v^2-39vd+18d^2=0 | | log(d)=0.44 | | (s/14)=p | | 7+42x=21x+(13) | | 5x-3=-8x+10 | | -23u^2+34=-32u^2+32 | | 2-(-4)+(-7)= | | u=4(7n+35)+7(n+1) | | 3ln(x-1)=-3 | | -10+1+7x=37 | | 11-(x+9)=9x-8 | | 38+n=66 | | 2f^2+9f+6=0 | | (4+u)(3u+2)=0 | | 28y+(y*y)+12=36 | | -2+2x=(-8)+(17x) | | 7g^2-8g+2=0 | | u=4(7*6+35)+7(6+1) | | 3x+11=(-49)-(9) | | 2t^3+3t^2-9t=0 | | 10=r+15 | | 20-4x=-2(x-2) | | x+0.5*15=161.25 | | 3(x-3)+4(x-4)=17 | | 26-5x=(6)-(10) |